‘I’m grown a man no doubt, I’ve broken bounds’—Robert Browning Crossing the Limits of Poetry - Jean-Charles Perquin (Cahiers Victoriens et Edouardiens)
This paper will focus on Robert Browning’s poetic writings, and especially on the way his poems were a constant crossroads of formal choices, from his very first publications to his last poem. He tried and questioned every form, every genre and every mode. His poetry was undeniably one of crossing. His poetry was never stable: as if he were impossible to satisfy or as if he never managed to create the ideal form, he systematically moved from one form to another, crossed, explored and combined genres and modes. Was it not one of the reasons why Oscar Wilde called him a ‘prose Browning’?